Legal developments in cross-border marriages among Malay muslims in Malaysia - Md Hashim, Noraini; Abdul Hak, Nora; Md Said, Helmi (International Islamic University Malaysia, 2015)
Cross-border marriages have received a considerable amount of attention in recent years. Patterns and characteristics of cross- border marriages appear to differ widely among the world’s region and races. This article aims to discuss the legal development and history of cross-border marriages from the perspective of Muslim Malay couples in Malaysia and generally, under the English law. An analytical legal approach is used in this study to explore the legal developments in such cross-border marriages. The findings of this work are expected to fill the gap in the legal literature on marriages in Malaysia and also provide reference for designing a new improved policy and regulatory framework to deal with the problem.